Hypoxic exposure can improve blood glycemic control in high-fat diet-induced obese mice - Park, Yeram; Jang, Inkwon; Park, Hun-Young; Kim, Jisu; Lim, Kiwon (Journal of exercise nutrition & biochemistry, 2020)
Blood glucose and insulin resistance were lower following hypoxic exposure in previous studies. However, the effect of hypoxia as therapy in obese model has not been unknown. Six-week-old mice were randomly divided into chow diet (n=10) and high-fat diet (HFD) groups (n=20). The chow diet group received a non-purified commercial diet (65 % carbohydrate, 21 % protein, and 14 % fat) and water ad libitum. The HFD group was fed an HFD (Research Diet, #D12492; 60% kcal from fat, 5.24 kcal/g). Both groups consumed their respective diet for 7 weeks. Subsequently, HFD-induced mice (12-weeks-old) were randomly divided into two treatment groups : HFD-Normoxia (HFD; n=10) and HFD-Hypoxia (HYP; n=10, fraction of inspired=14.6%). After treatment for 4 weeks, serum glucose, insulin and oral glucose tolerance tests (OGTT) were performed. Homeostatic model assessment values for insulin resistance (HOMA-IR) of the HYP group tended to be lower than the HFD group. Regarding the OGTT, the area under the curve was 13% lower for the HYP group than the HFD group. Insulin resistance tended to be lower and glucose uptake capacity was significantly augmented under hypoxia. From a clinical perspective, exposure to hypoxia may be a practical method of treating obesity.